The Remission Effects of First Injection of Sclerotherapy for Pediatric Rectal Prolapse: A Systematic Review and Meta-Analysis - Zhou, Weimo; Shi, Yingzuo; Zhang, Ming; Li, Li (Frontiers in Surgery, 2022)
Background: Pediatric rectal prolapse is a common issue for the clinical practice. Among the various managements, the sclerotherapy is an important method to successfully treat pediatric rectal prolapse, especially for the first injection. The knowledge of first injection of sclerotherapy can be revealed by a systemic review and meta-analysis of randomized clinical trials. Methods: We performed a systematic search and a meta-analysis for the retrospective clinical studies of sclerotherapy in the pediatric rectal prolapse. The comparison between remission and recurrence after the first injection of sclerotherapy was performed to find if the first injection of sclerotherapy can treat rectal prolapse completely. After restricted selection, 17 studies, 1091 pediatric rectal prolapse subjects with sclerotherapy were enrolled in a variety of classifications of injection agent. The focused outcome was that if the first injection of sclerotherapy can achieve remission status. The meta-analysis was performed by Review Manager 5.4. Results: Among the subjects receiving sclerotherapy, the meta-analysis favors the remission status after receiving the first injection of sclerotherapy. The meta-analysis results showed significant remission tests for overall effect and significant heterogeneities in odds ratio and fixed-effects model. The significant therapeutic effects still remained even testing in the relative risk and random-effects model. Conclusions: In spite of significant heterogeneity and relatively low quality of evidence, the first injection of sclerotherapy might demonstrate the therapeutic effects to help the patients of pediatric rectal prolapse achieve remission status.